2004
DOI: 10.1175/bams-85-2-237
|View full text |Cite
|
Sign up to set email alerts
|

Major Advances Foreseen in Humidity Profiling From the Water Vapour Lidar Experiment in Space (Wales)

Abstract: The first active humidity profiling system in space is being developed by the European Space Agency (ESA) in the horizon of 2010. Data quality in terms of vertical resolution, accuracy, low bias, and vertical extent is expected to be unsurpassed. There are pressing needs for high-quality water vapor observations to fulfill societal and scientific requirements in environmental understanding and operational weather prediction. At one level, these needs arise from requirements for more reliable information about … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 44 publications
0
24
0
Order By: Relevance
“…In 2007, the annual global cloud-free fraction was 53.5%, suggesting that the retrieved water vapor profiles of a space-based DIAL could extend down to the surface for over half of the total retrieved profiles and thereby substantially add value to the next generation of atmospheric remote sensors targeting tropospheric dynamics Surv Geophys ( ) 38:1445Geophys ( -1482Geophys ( 1451 Atmospheric Sounding Interferometer). The results of the study indicated that for a fixed error threshold, the WALES water vapor DIAL concept under study would extend water vapor measurements to higher altitudes than for IASI, with improved vertical resolution near the surface (Gerard et al 2004). Di Girolamo et al (2008) also carried out an end-toend simulation of a WALES like lidar to assess the systematic and random error performance under a wide range of atmospheric conditions.…”
Section: Measurement Capabilitiesmentioning
confidence: 95%
See 2 more Smart Citations
“…In 2007, the annual global cloud-free fraction was 53.5%, suggesting that the retrieved water vapor profiles of a space-based DIAL could extend down to the surface for over half of the total retrieved profiles and thereby substantially add value to the next generation of atmospheric remote sensors targeting tropospheric dynamics Surv Geophys ( ) 38:1445Geophys ( -1482Geophys ( 1451 Atmospheric Sounding Interferometer). The results of the study indicated that for a fixed error threshold, the WALES water vapor DIAL concept under study would extend water vapor measurements to higher altitudes than for IASI, with improved vertical resolution near the surface (Gerard et al 2004). Di Girolamo et al (2008) also carried out an end-toend simulation of a WALES like lidar to assess the systematic and random error performance under a wide range of atmospheric conditions.…”
Section: Measurement Capabilitiesmentioning
confidence: 95%
“…Unfortunately, WALES was not selected for further development due to cost and technical risk associated with the laser under consideration; however, several feasibility studies were carried out and demonstrated the utility of such measurements for weather and climate applications. A concept study by Gerard et al (2004) assessed the performance of a space-based water vapor DIAL relative to passive infrared measurements such as from IASI (Infrared Fig. 3 Global map of annual mean CALIPSO-derived cloud-free fraction.…”
Section: Measurement Capabilitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the differential absorption lidar (DIAL) technique applied from satellites shows high potential to meet those requirements [7][8][9] there is need for an exploratory satellite mission demonstrating high-vertical resolution water vapor profiles by active remote sensing [5]. In recent years several lidar missions have thus been proposed to measure water vapor profiles from space [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…It is based on the comparison of the lidar signals at two wavelengths, one coinciding with a water-vapour absorption line of adequate strength and the second sufficiently far away from any line not to undergo substantial absorption. The quality of the data obtained from ground-based [5,6] and airborne [7][8][9][10] instruments in terms of vertical resolution, precision and accuracy indicates the feasibility of a space-borne instrument [11], from which major advances in humidity profiling with global coverage are expected [12]. While ground-based water-vapour DIALs operate at two wavelengths only (one on-line and the other off-line), space-borne instruments may operate at a set of different on-line wavelengths corresponding to absorption lines of different strengths, thus providing different penetration depths in the atmosphere.…”
mentioning
confidence: 99%